Inter-segmental coordination during a unilateral 180° jump in elite rugby players: Implications for prospective identification of injuries - Krajewski, K. T.; McCabe, C.; Sinnott, A. M.; Moir, G. L.; Lamont, H. S.; Brown, S.; Connaboy, C. (Applied Sciences, 2020)
Musculoskeletal injuries often occur during the execution of dynamic sporting tasks that involve rotation. The prescription of appropriate prevention strategies of musculoskeletal injury relies on assessments to identify risk, but current assessment tools focus on uniplanar movements. The purpose of this paper is to demonstrate the utility of the unilateral 180° jump as a potential assessment tool for injury risk in the lower body by (1) providing descriptive kinematics of the knee, thigh, and pelvis (2) conducting inter-segmental coordination analysis, and (3) comparing the knee kinematics between the dominant and non-dominant limb (NDL) during the loading (LOP) and landing phase (LAP). Elite rugby players completed one session, performing five 180° unilateral jumps on each limb while collecting kinematic data. Independent t-tests were used to compare peak angles of DL and NDL. Continuous Relative Phase (CRP) plots were constructed for thorax and pelvis in the transverse plane. At the loading phase, the non-dominant limb had greater peak knee abduction (ABD) (p = 0.01). At the landing phase, the dominant limb had greater peak knee adduction (ADD) (p = 0.05). At the landing phase, the non-dominant limb had greater peak knee ABD (p = 0.01). CRP plots indicate participants can utilize a thorax-led, pelvis-led, or synchronized rotational method. Bilateral asymmetries were observed, indicated by significant differences in the bilateral landing phase peak ADD/ABD, which is of particular interest considering all participants were healthy. Therefore, additional research is needed to determine thresholds for injury risk during rotational tasks.